2016
DOI: 10.18632/oncotarget.9622
|View full text |Cite
|
Sign up to set email alerts
|

Functional and prognostic significance of long non-coding RNA MALAT1 as a metastasis driver in ER negative lymph node negative breast cancer

Abstract: MALAT1 (metastasis associated lung adenocarcinoma transcript1) is a conserved long non-coding RNA, known to regulate gene expression by modulating transcription and post-transcriptional pre-mRNA processing of a large number of genes. MALAT1 expression is deregulated in various tumors, including breast cancer. However, the significance of such abnormal expression is yet to be fully understood. In this study, we demonstrate that regulation of aggressive breast cancer cell traits by MALAT1 is not predicted solely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 99 publications
5
128
0
5
Order By: Relevance
“…MALAT has been found to be highly overexpressed in several human malignancies and has been associated with tumor invasion and metastasis in various cancers. [78][79][80][81][82][83][84] Jiao et al 78 reported that MALAT1 could increase the proportion of pancreatic CSCs, maintain self-renewal capacity, decrease chemosensitivity to anticancer drugs and promote angiogenesis in vitro in pancreatic cancer cell lines. Downregulation of MALAT1 reduced self-renewal-associated factors, such as SOX2, Bmi and Nanog.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
“…MALAT has been found to be highly overexpressed in several human malignancies and has been associated with tumor invasion and metastasis in various cancers. [78][79][80][81][82][83][84] Jiao et al 78 reported that MALAT1 could increase the proportion of pancreatic CSCs, maintain self-renewal capacity, decrease chemosensitivity to anticancer drugs and promote angiogenesis in vitro in pancreatic cancer cell lines. Downregulation of MALAT1 reduced self-renewal-associated factors, such as SOX2, Bmi and Nanog.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
“…LncRNAs are defined as transcripts longer than 200 nucleotides with no protein-coding potential. To date, several lncRNAs have been found to be dysregulated in breast cancer and to be closely associated with the diagnosis and prognosis of breast cancer, such as metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ), nuclear enriched abundant transcript 1 ( NEAT1 ), and breast cancer antiestrogen resistance 4 ( BCAR4 ) [567]. LncRNA taurine upregulated gene 1 ( TUG1 ) was initially identified as an essential gene for retinal development in the developing mouse eye [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNA HOX transcriptantisense RNA (HOTAIR) functions as an oncogene and an independent biomarker for diagnosis and prognosis prediction in various tumors including hepatocellular carcinoma1718, lung cancer1920, gastric cancer2122, and colorectal cancer23. LncRNA metastasis-associated in lung adenocarcinoma transcript 1 (MALAT1) can also be used as a prognostic factor for survival and metastasis in various cancers7242526. H19 is aberrantly regulated in a great deal of cancers, it can serve as a biomarker for poor prognosis in patients with several tumor types2728 as well.…”
mentioning
confidence: 99%